2003
DOI: 10.1046/j.1445-5994.2003.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Health and stress in Australian interns

Abstract: Over a 3-year period, interns completed questionnaires on self-reported health and stress during their orientation week at the beginning of the year, during mid year, and at the end of the first year. Interns experienced increased levels of stress and ill health in the middle of the year as compared with the start and end of the year (chi2=11.9, P=0.003 and chi2=20.4, P<0.001, respectively). Despite workplace reform for junior doctors, this study suggests that interns still feel overburdened with work expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…25 But only a few reports have been published about stress and depression levels among interns. 26 In our study, majority of junior doctors (40.35%) were having severe and extremely severe anxiety level, when compared to those (11.40%) who experienced severe and extremely severe depression and those (9.65%) who had severe and extremely severe stress which was consistent with the other studies stating that marked amount of anxiety was found among the junior doctors.…”
Section: Discussionsupporting
confidence: 81%
“…25 But only a few reports have been published about stress and depression levels among interns. 26 In our study, majority of junior doctors (40.35%) were having severe and extremely severe anxiety level, when compared to those (11.40%) who experienced severe and extremely severe depression and those (9.65%) who had severe and extremely severe stress which was consistent with the other studies stating that marked amount of anxiety was found among the junior doctors.…”
Section: Discussionsupporting
confidence: 81%
“…Willcock et al point out that there is an increase in psychiatric morbidity over the intern period in first‐year medical graduates. This corroborates the findings of a larger study we conducted among interns during their first year, in which we showed that psychiatric morbidity rises, particularly during the middle of this first year as a doctor, but then decreases by the end of the year 2 …”
supporting
confidence: 91%
“…It is well established that junior doctors are vulnerable to psychological ill health and that a considerable number suffer from depression and disillusionment (Newbury-Birch andKamali 2001, Pesce 2009), particularly during their internship (Bruce, Thomas, and Yates 2003). Bellini et al (2002) found that interns had high levels of energy and vigor when they started their internship, but after five months they were depressed, angry, and suffering from fatigue.…”
Section: Burnout and Depressionmentioning
confidence: 99%